An Observational Correlational Study Between Sattvabala (Mind Strength) and Achievement Motivation Among Students - Fulzele Vanita C,; Nagdeve Pranali A, (International Journal of Ayurveda and Pharma Research, 2022)
Sattvabala (strength of mind) provides an adequate status of well being of a person, thus giving a systemic and holistic approach to understand a student. Acharya charak describes that, an excellent student should be of Pravara sattva (with dominance of Sattva Guna). Achievement Motivation is a consistent striving force of an individual to achieve success to a certain standard of excellence in a competing situation. By assessing, improving and stabilizing student's Sattvabala, we can reach in depth of their achievement motivation and thereby guide for the improvement in academic performance and achieving career goals. Considering the above facts, this observational survey study among students was undertaken. Aim- To study Sattvabala and achievement motivation among students and find a correlation between them. Methodology- In this descriptive survey research study total 120 students, course wise categorized into 4 groups, 30 students from each course were taken from different Maharashtrian educational institutions. For the assessment of Sattvabala and achievement motivation, self made questionnaires and 'DEO-Mohan Achievement Motivation (n-Ach) Scale (DMAMS)' were used respectively. Data analysis done with the percentage and Pearson's correlation coefficient. Result- Sattvabala and achievement motivation are highly significantly correlated with each other (0.9094). Conclusion- To know the achievement motivation factor of students, examination of Sattvabala from Ayurveda context will prove a definite useful tool. Ayurveda Sattvavajay concept, yoga, Ayurveda Medhya (brain booster) drugs, Achar rasayan, Sadvritta (Ayurveda codes and conducts) can be used to improve the Madhyam and Avara Sattvabala students to improve their achievement motivation and thereby this will definitely prove helpful to achieve their life goals.